Hypertensive Disorders of Pregnancy: An Ongoing Holocaust - Borade, Pratima V; Haralkar, Santosh J; Wadagale, Atul V (National Journal of Community Medicine, 2014)
Background: Hypertensive disorders of pregnancy (H.D.P.) can lead to serious complications for both mother and fetus in her womb. Objective: To determine prevalence and some epidemiological factors of hypertensive disordersof pregnancy. Material and Methods: Present study conducted on pregnant women attending antenatal clinicin medical college.It was a cross- sectional study. Information was obtained by face-to-faceinterviews of study subjects. Results:Out of 1566 randomly selected study subjects, 95(6%) were hypertensive. Out of 95hypertensive pregnant women 63.3% were diagnosed as pre-eclampsia, 21.1% as gestationalhypertension, 11.5% as eclampsia and 4.1% as chronic hypertension. H.D.P. is common inwomen with age group >33yrs (20%), who arelabourer(13.2%). It is more prevalent in third trimester(11.1%) of pregnancy and in grandmultiparas (21.6%). Conclusion: Hypertensive disorders of pregnancy are one of the common medical complicationsworsening the outcome of pregnancy.